SALES PULSA VOUCHER CELLULAR MEDIA ON APPLICATION ON USING MICROSOFT VISUAL BASIC 6.0 - Fajri Ramadhan Faisal; Rahayu Noveandi, Skom, MM (Jurnal Sistem Informasi, 2007)
In scientific writing, the writer explains the design of application programs on the MediaCellular voucher sales by using Microsoft Visual Basic 6.0. In this application programconsists of 7 Form. And use the Data Access Object program to connect to the database.And using Microsoft Access 1997 for database.